(Ré)écrire le mythe d’Hydro-Québec: Les murailles d’Erika Soucy - Massicotte, Isabelle Kirouac (Ponti/Ponts, 2021)
Québec’s collective memory is characterised by strong symbols of national identity, such as nature, including water, possibly the component that stroke the most the collective imaginary. Water is associated with a great and vital source of energy: hydro-electricity. In Québec, this form of energy is provided and managed by Hydro-Québec, which occupies an important role in the québécois collective narrative, because the public enterprise is closely linked to the ‘Révolution tranquille’. The importance of the corporation translates into a great number of studies achieved by researchers from various backgrounds: Stéphane Savard in history, Caroline Desbiens in geography and Dominique Perron in literature. However, Perron studied Hydro-Québec’s promotional materials, and not the company’s representations in literary works. With this paper, my intention is to provide a reading of a contemporary narrative of Hydro-Québec in Québec’s literature. To do so, I will discuss Hydro-Québec’s myth in Les murailles (2016), a novel by Erika Soucy.